ChemInform Abstract: One‐Pot Synthesis and Sigma Receptor Binding Studies of Novel Spirocyclic‐2, 6‐diketopiperazine Derivatives. Issue 37 (August 2016) - Ghandi, Mehdi; Sherafat, Fatemeh; Sadeghzadeh, Masoud; Alirezapour, Behrouz
Abstract: The title compounds are prepared from benzoic acids, cyclic ketones, ethylglycinate hydrochloride, and cyclohexyl isocyanide by an one‐pot, two‐step sequential Ugi/intramolecular N‐amidation process.